1 Microstructural & microvascular phenotype of hypertrophic cardiomyopathy – from mutation to hypertrophy; a multicentre collaborative study of 192-subjects. (28th January 2023) - Joy, G; Kelly, CI; Webber, M; Pierce, I; Teh, I; Schneider, JE; Nguyen, C; Kellman, P; Hughes, RK; Velazques, P; Das, A; Tomé, M; et al.
Abstract : Introduction: Microvascular disease (MVD) and disarray are myocardial substrates that associate with adverse events in HCM. How these relate to sarcomeric mutation and LVH are poorly understood. Advances in CMR allow disarray and MVD to be detected and quantified. We aimed to investigate their prevalence and severity as phenotype evolves. Materials and Methods: 89 patients with overt HCM, (44 G+LVH+, 45 G-LVH+), 75 individuals with sarcomeric mutations and no LVH (G+LVH-) and 28 healthy volunteers (HV) underwent quantitative adenosine stress perfusion CMR and cardiac diffusion tensor imaging (cDTI) (measuring fractional anisotropy (FA), mean diffusivity (MD) and Second Eigenvector Angle (E2A)). Results: Demographics were as follows: HCM: Age 56(47–61) years, female 21%, G+LVH-: Age 34(24–41), female 55%, HV: Age 34(32–40) years and female 50%. Patients with overt HCM had more disarray compared to both G+LVH- and HV (lower FA:0.28±0.03 vs FAG+LVH- 0.32±0.02 p<0.001, higher MD:1.57±0.08 × 10 -3 mm 2 /s vs MDG+LVH- 1.50±0.05 × 10 -3 mm 2 /s, p<0.001 and higher E2A60±9° vs E2AG+LVH- 49±9° p<0.001). When considering G+LVH+ vs G-LVH+, there was no significant differences in FA, or MD, however G-LVH+ adopted steeper systolic sheetlet angles compared to G+LVH+ (62±6° vs 58±11° p=0.047). Compared to G+LVH-, overt HCM had lower stress MBF (1.7±0.5 vs 2.5±0.5ml/g/min p<0.001) and a higher prevalence of perfusion defects (91%(84)vs 27%(19) p<0.001). Perfusion defects were ubiquitous in G+LVH+, occurring in all 44 patients but only 84%(35) in G-LVH+ p=0.005. Compared to HV, G+LVH- had lower FA (0.32±0.02 vs 0.34±0.02 p<0.001), higher MD (1.50±0.05 × 10 -3 mm 2 /s vs 1.48±0.04 × 10 -3 mm 2 /s p<0.001 and higher E2A (49±9° vs 40±9° p<0.001). Compared to HV, G+LVH- had no significant difference in global stress perfusion values, and a higher prevalence of perfusion defects (25%(19) vs 0 HV p=0.005). G+LVH- with perfusion defects had lower FA than G+LVH- without perfusion defects (0.31±0.3 vs 0.32±0.02 p=0.018). Conclusion: MVD and disarray are present, detectable and associate in G+LVH-. Overt HCM is characterised by more myocyte disarray and MVD than both G+LVH- and health. Subtle differences in MVD and disarray occur between G+LVH+ and G-LVH+ with perfusion defects being ubiquitous in genotype positive HCM.